Experimental transmission of Anaplasma marginale by male Dermacentor reticulatus - Zivkovic, Zorica (BioMed Central, 2007)
BACKGROUND: Bovine anaplasmosis has been reported in several European countries, but the vector competency of tick species for Anaplasma marginale from these localities has not been determined. Because of the wide distributional range of Dermacentor reticulatus within Europe and the major role of Dermacentor spp. as a vector of A. marginale in the United States, we tested the vector competency of D. reticulatus for A. marginale. RESULTS: Male D. reticulatus were allowed to feed for 7 days on a calf persistently infected with a Zaria isolate of A. marginale, after which they were removed and held off-host for 7 days. The ticks were then allowed to feed a second time for 7 days on a susceptible tick-naïve calf. Infection of calf No. 4291 was detected 20 days post exposure (p.i.) and confirmed by msp4 PCR. Thirty percent of the dissected acquisition fed ticks was infected. In addition, A. marginale colonies were detected by light microscopy in the salivary glands of the acquisition fed ticks. Transmission of A. marginale to calf No. 9191 was confirmed by examination of Giemsa-stained blood smears and msp4 PCR. Ticks were dissected after transmission feeding and presence of A. marginale was confirmed in 18.5% of the dissected ticks. CONCLUSION: This study demonstrates that D. reticulatus males are competent vectors of A. marginale. Further studies are needed to confirm the vector competency of D. reticulatus for other A. marginale strains from geographic areas in Europe.